Effective muscle elongation positions for the neck extensor muscles: An ultrasonic shear wave elastography study. (October 2021) - Yanase, Ko; Ikezoe, Tome; Nakamura, Masatoshi; Saeki, Junya; Yagi, Masahide; Hirono, Tetsuya; Tamezawa, Toru; Motomura, Yoshiki; Ibuki, Satoko; Ichihashi, Noriaki
Abstract: This study aimed to clarify the effective stretching positions for neck extensor muscles. Fifteen healthy men were measured shear moduli of the right neck extensor muscles using ultrasound shear wave elastography in following positions: rest (Rest), flexion (Flex), contralateral bending (Bend), flexion + contralateral bending (Flex → Bend), flexion + contralateral bending + contralateral rotation (Flex → Bend → ConRot), and flexion + contralateral bending + ipsilateral rotation (Flex → Bend → IpsRot). The increase in the shear modulus indicated a greater muscle elongation. Regarding the upper trapezius and splenius capitis, the shear moduli at Flex → Bend, Flex → Bend → ConRot, and Flex → Bend → IpsRot were significantly higher than those at Rest. The shear moduli at stretching positions, including contralateral bending, were significantly higher than those at Rest and Flex in the levator scapulae. The results indicated that the stretching position with a combination of flexion and contralateral bending could be effective for elongation of the upper trapezius and splenius capitis. Furthermore, the stretching positions including contralateral bending could be effective for the levator scapulae.